Literacka historia ołowiu. Rekonesans - Tomczok, Marta (Narracje o Zagładzie [czasopismo zamknięte], 2021)
This article offers an overview and preliminary arrangements of literary texts, chosen paintings and films (most of them from the past three centuries) which feature the motif of lead. The presence of lead as a symbol has been detected in poetry which treated the problem of war and peace; occasionally this use of lead has occurred in relation to printing, typesetting, and – less frequently – children’s toys. Much more often the motif of lead has been used in literary works to introduce the topic of melancholia and to express artists’ interest in alchemy. An analysis of literary prose at the turn of the 20th century related to zinc and lead metallurgy shows that lead did not occur in the context of mining, chemistry, and medicine until the 19th century. On the basis of studies of the press, historical literature, and contemporary reportage, the article shows the toxic nature of lead and its harmful effect on people and the environment, about which artists and authors try to warn the public at the turn of the 21st century. The article shows that the parallel between melancholia and saturnism is a well-documented phenomenon.